Nucleotide sequence and regulation of a new putative cell wall hydrolase gene, cwlD, which affects germination in Bacillus subtilis. . - Sekiguchi, J (1995)
DNA sequencing of a region upstream of the mms223 gene of Bacillus subtilis showed the presence of two open reading frames, orf1 and orf2, which may encode 18- and 27-kDa polypeptides, respectively. The predicted amino acid sequence of the latter shows high similarity to a major autolysin of B. subtilis, CwlB, with 35% identity over 191 residues, as well as to other autolysins (CwlC, CwlM, and AmiB). The gene was tentatively named cwlD. Bright spores produced by a B. subtilis mutant with an insertionally inactivated cwlD gene were committed to germination by the addition of L-alanine, and spore darkening, a slow and partial decrease in A580, and 72% dipicolinic acid release compared with that of the wild-type strain were observed. However, degradation of the cortex was completely blocked. Spore germination of the cwlD mutant measured by colony formation after heat treatment was less than 3.7 x 10(-8). The germination deficiency of the cwlD mutant was only partially removed when the spores were treated with lysozyme. Analysis of the chromosomal transcription of cwlD demonstrated that a transcript (RNA2) appearing 3 h after initiation of sporulation may have originated from an internal sigma E-dependent promoter of the cwlD operon, and a longer transcript (RNA1) appearing 4.5 h after sporulation may have originated from a sigma G-dependent promoter upstream of the orf1 gene. The cwlD mutant harboring a B. subtilis vector plasmid containing the intact cwlD gene recovered germination at a frequency 26% of the wild-type level.